Evaluasi Kematangan Investasi SI/TI Menggunakan Kerangka ITIM (Studi Kasus Universitas Negeri Manado) - Alfrina Mewengkang; Lukito Edi Nugroho; Dani Adhipta (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
IT investments can be profitable and also harmfull for the organization. To get the value of information technology (IT), it takes more than just an investment but also need IT intelligence itself. One way to assure the investment done properly and provides benefits to the Universitas Negeri Manado (UNIMA) is to measure the maturity level of IT investment management. This research measures the maturity level of IS/IT investment management at UNIMA using Information Technology Investment Management (ITIM) method. ITIM is commonly used for organizational improvement by providing a roadmap that agencies can use for improving their investment management processes by describing the critical process in each stage of maturity to simplify evaluation. The results of these measurements, the maturity level of IS/IT investment management at UNIMA is at level 1. There are several key processes that are not fulfilled for entry to level 2. By knowing a picture of the IT investment management today, recommendations to improve investment management processes can be given.